Some questions about the elite of "Carteia" - Padilla Monge, Aurelio (Gerión. Revista de Historia Antigua, 2012)
The anthroponomastic analysis of the members of the oligarchy of Carteia proves the existence of most descendants from the Hispano-Roman people to whom Livy (43.3.2) refers, or from incomers who arrived later from Italy. Nevertheless, this analysis also shows the presence of some descendants from the inhabitants of Punic Carteia who chose to live in the new Latin colony (Livy, 43.3.4).